(untitled) - Dominika Kohanová; Žaneta Hrbková; Katarína Žiaková (University of Ostrava, 2024)
Aim: To determine the level of teamwork among nursing staff in a selected teaching hospital and identify factors that influence the level of teamwork. Design: A descriptive cross-sectional study. Methods: The sample included 292 nursing staff working in a teaching hospital in the Žilina region of Slovakia. Data collection was carried out between April and June 2022 using the Nursing Teamwork Survey (NTS). Data were analyzed using descriptive and inferential statistics. Results: The mean score for the NTS was 2.87 (SD = 0.56) demonstrating a positive perception of teamwork less than 75% of the time. The highest evaluated subscale was the shared mental model (3.23 ± 0.62). Differences were found in the evaluation of teamwork according to education, job position, working hours, total and current professional experience, intention to leave, and staffing adequacy. The correlation analysis revealed associations between teamwork and variables related to satisfaction and quality and safety evaluation. Several variables predicted the general evaluation of teamwork (p < 0.05). Conclusion: The evaluation of teamwork may point to its different perception among members of nursing teams. It may also help to identify strengths and weaknesses of nursing teams and, consequently, to implement effective techniques focused on improving teamwork and, thus, the quality of nursing care in hospitals.